A Glucagon-like Peptide 1 Analog Protects Mitochondria and Attenuates Hypoxia–Reoxygenation Injury in Cultured Cardiomyocytes. Issue 4 (April 2022) - Kobara, Miyuki; Toba, Hiroe; Nakata, Tetsuo
Abstract: Glucagon-like peptide 1 (GLP-1) analogs improve glycemic control in diabetes and protect the heart against ischemia–reperfusion injury. However, the mechanisms underlying this protection remain unclear. Mitochondria are essential for myocyte homeostasis. Therefore, we herein examined the effects of a GLP-1 analog on mitochondria after the hypoxia–reoxygenation of rat neonatal cultured cardiomyocytes. Cardiomyocytes were subjected to hypoxia for 5 hours followed by reoxygenation for 30 minutes in the presence or absence of exendin-4 (50 nmol/L), a GLP-1 analog. Hypoxia–reoxygenation increased lactate dehydrogenase and caspase-3 activities, indicators of lethal myocyte injury and apoptosis, respectively, and exendin-4 attenuated these increases. The content of ATP in myocytes decreased after hypoxia–reoxygenation but was preserved by exendin-4. The membrane potential and shape of mitochondria were assessed using a fluorescent probe. Exendin-4 attenuated the hypoxia–reoxygenation–induced disruption of the mitochondrial membrane potential and shortening. Mitochondrial quality control–related factors, such as optic atrophy protein 1, mitofusin 2, dynamin-related protein 1, and parkin, were examined by Western blotting. Exendin-4 significantly increased the expression of the fusion proteins, optic atrophy protein 1 and mitofusin 2, and decreased that of the mitophagy-related protein, parkin, without altering dynamin-related protein 1 expression levels. Exendin-4 also preserved Akt phosphorylation levels after hypoxia–reoxygenation, whereas wortmannin, an inhibitor of the phosphoinositide 3-kinase–Akt pathway, blunted exendin-4–induced myocyte protection and its effects on mitochondrial quality control factors. In conclusion, exendin-4 protected mitochondria by preserving the phosphorylation of Akt and fusion proteins, leading to the attenuation of hypoxia–reoxygenation–induced injury in cultured myocytes.